Children Victims Trauma Healing of Sinabung Mountain Eruption - Ameilia Zuliyanti Siregar; Husmiati Husmiati (Jurnal Penelitian Kesejahteraan Sosial, 2016)
This essay writen based on research on trauma healing among children victims of Sinabung eruption in North Sumatra. Research method was survey and sixty children victims of Sinabung eruption were chosen as respondents. Traumahealing handling done by a coordinated and integrated between the involvement of the whole society, NGOs, businesses and government agencies. The research found that 60 respondents 47.69 persen were boys and 52.31 persen were girls.Level of education, from primary school 76.93 persen, junior high school 15.38 persen and senior high school was 7.68 persen. The distributed questioaires answered by respondents showed there were three sacales, namely children stress symtom, children traumatic symtom, and violent symptom at refugees camps which were still be tolerated in numbers. Availability of psychological treatments were trauma healing, like singing, dancing, and drawing. It is suggested to the goverment, especially Ministry of Education, Ministry of Social Affairs, and related agencies in providing assistance to the victims should conduct an analysis on the rght benefit and target.